Peningkatan Keterampilan Menulis Bahasa Indonesia Siswa: Pendekatan Metode Demonstrasi dalam Meningkatkan Hasil Belajar - Uselina Polinda Demetou (Yayasan Perguruan Kampus, 2023)
Indonesian language education in elementary schools should produce learning outcomes in the form of changes in knowledge and skills that are in line with the institutional goals of elementary schools. Based on observations, many students cannot write well. This can be seen from the results of learning Indonesian language subjects, especially writing material. Meanwhile, it can be seen that many students' learning activities in learning Indonesian have not yet reached the completeness set by the school. Apart from that, it can be seen that students at SD Negeri Inauga Sempan Timika are very lacking in the practice of writing texts, so that students' daily assessment results are low. The aim of this research is to improve the writing skills of Inauga Sempan Timika Elementary School students using the demonstration method. shows that learning by demonstration has a positive impact in increasing student learning achievement which is marked by increasing student learning completeness in each cycle, namely cycle I (69%), and cycle II (83,335). The application of the demonstration learning method has a positive influence, namely it can increase students' learning motivation as shown by the results of research using the demonstration learning method so that they become motivated to learn to write, especially in learning Indonesian.